Energy system transition pathways to meet the global electricity demand for ambitious climate targets and cost competitiveness. (1st February 2023) - Aghahosseini, Arman; Solomon, A.A.; Breyer, Christian; Pregger, Thomas; Simon, Sonja; Strachan, Peter; Jäger-Waldau, Arnulf
Highlights: 9 global transition pathways are analysed for decarbonisation of electricity sector. Input-output data of simulation models are remodelled by a cost-optimisation model. The least-cost, highly diversified, and business-as-usual pathways are compared. Pace, CO2 costs and energy diversity are found crucial across the scenarios. Ambitious paths show competitive costs, ranging between 45.2 and 59.2 €/MWh by 2050. Abstract: This study presents a novel energy system modelling approach for the analysis and comparison of global energy transition pathways for the decarbonisation of the electricity sector. The results of the International Energy Agency (IEA), and the Teske/DLR scenarios are each reproduced. Additionally, five new energy transition trajectories, called LUT, are presented. The research examines the feasibility of each scenario across nine major regions in 5-year intervals, from 2015 to 2050, under a uniform modelling environment with identical technical and financial assumptions. The main differences between the energy transition paths are identified across: (1) the average electricity generation costs; (2) energy diversity; (3) system flexibility; (4) energy security; and, (5) transition dynamics. All LUT and Teske/DLR scenarios are transitioned to zero CO2 emissions and a 100% renewable energy system by 2050 at the latest. Results reveal that the LUT scenarios are the least-cost pathways, while the Teske/DLR scenarios are centred around energy diversity with slightly higher LCOE of around 10–20%. The IEA shares similarities with the Teske/DLR scenarios in terms of energy diversity yet depends on the continued use of fossil fuels with carbon capture and storage, and nuclear power. The IEA scenario based on current governmental policies presents a worst-case situation regarding CO2 emissions reduction, climate change and overall system costs.